2021
DOI: 10.1097/md.0000000000023977
|View full text |Cite
|
Sign up to set email alerts
|

The risk factors for cognitive dysfunction in elderly patients after laparoscopic surgery

Abstract: Postoperative cognitive dysfunction (POCD) is very common in clinical settings, it is necessary to analyze the risk factors for POCD in elderly patients after laparoscopic surgery to provide insights into clinical surgery management. Elderly patients undergone laparoscopy between September 1, 2018 and March 31, 2020 were included. The mini-mental state examination (MMSE) scale was used to evaluate the POCD, and the characteristics and clinical data of patients with and without POCD were collected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
(20 reference statements)
0
11
1
Order By: Relevance
“…Prolonged surgery duration may lead to increased blood loss and inflammatory responses, as well as increased use of anesthetic drugs. As shown in numerous studies, the duration of the operation affects the occurrence of POCD [43]. However, no correlation between the time of operation and the occurrence of POCD was observed in our study.…”
Section: Discussioncontrasting
confidence: 75%
“…Prolonged surgery duration may lead to increased blood loss and inflammatory responses, as well as increased use of anesthetic drugs. As shown in numerous studies, the duration of the operation affects the occurrence of POCD [43]. However, no correlation between the time of operation and the occurrence of POCD was observed in our study.…”
Section: Discussioncontrasting
confidence: 75%
“…Polypharmacy can also contribute. Severe acute deteriorations including electrolyte disturbances, vitamin deficiencies such as severe hypovitaminosis D [42], hypotension, sleep deprivation, renal failure, liver failure, stroke, and acute trauma can precipitate delirium [3,43]. Long duration of surgery, transfusions, and cardiac surgery, especially with the use of cardiopulmonary bypass [44], are common surgical risk factors.…”
Section: Potential Risk Factorsmentioning
confidence: 99%
“…This may be related to the short duration of controlled hypotension and surgery in this study. Some studies also revealed that longer duration of surgery (OR1.82, 1.01∼3.16) were risk factors for POCD ( 19 ). A randomized trial shown that BIS decreases delayed neurocognitive recovery and postoperative neurocognitive disorder ( 20 ).…”
Section: Discussionmentioning
confidence: 99%